Brain electrical activity during bench press weight training exercise - Engchuan, Pipat; Wongsuphasawat, Karnt; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2019)
Background: Weight training is one type of exercises which some people interest. When the body has a physical exercise with enough intensity, it can produce a positive effect on brain function by changing amplitude of electroencephalographic activity. Aims and Objective: The purpose of this investigation was to examine a more comprehensive range of the electroencephalographic activity including delta, theta, alpha, beta, and gamma brainwaves during bench press weight training exercise. Materials and Methods: Electroencephalographic activities were recorded with nine participants by using the commercial lightweight electroencephalographic device, NeuroSky Mindwave Mobile, both before and during bench press weight training exercise. Results: The present study was conducted to find out how bench press weight training exercise effected to human brainwave. The electroencephalographic activity could be recorded during bench press weight training. The findings of the present study documented increase in beta and gamma brainwaves during bench press weight training exercise. This electrophysiological changes could represent the rearrangement of different systems as a consequence of exercise. Conclusion: This bench press weight training might significantly alter the intense exercise. Future studies may want to examine how these changes in electroencephalographic activity influence or are associated with changes in cognition, affect and/or perception during/after bench press weight training exercise. The impact of peripheral physiology on electroencephalographic activity of bench press weight training exercise also needs to be examined.